Reproduction of Centropomus undecimalis and C. ensiferus (Perciformes: Centropomidae) in a tropical coastal lagoon - Gassman, Juan Pablo; López-Rojas, Héctor; Padrón, Dana (Revista de Biología Tropical, 2017)
Snooks C. undecimalis and C. ensiferus are important fishery resources in their distribution area. In Venezuela they are caught by artisanal fisheries along the entire coast. However, studies on their biology that would help establish fishing regulations are scarce. To study reproduction aspects of these species, we analyzed 1 325 individuals of C. undecimalis and 2 025 of C. ensiferus caught by artisanal fishing in the Laguna de Tacarigua in Northern Venezuela, from July 2009 to September 2010. Total length, total weight, sex and stage of gonadal development were recorded. The sex ratio varied throughout the year: there was a significant difference in favor of C. undecimalis males (1.5:1), and C. ensiferus females (1:3.3). Differences were also evident in the sexual proportion at each size group. For both species, males dominated in the lower size ranges while females dominated in the larger size ranges. These results suggested sequential hermaphroditism (protrandry) in both species. Size at sexual maturity (Lm50) for C. undecimalis was ♀= 73.6 and ♂= 59.3 cm, and ♀= 26 and ♂= 21.5 cm for C. ensiferus. C. ensiferus reproduced throughout the year with two periods of higher intensity (August to September and February to April). Although we found very few mature individuals for C. undecimalis, February showed an important reproduction peak. Growth differences were found between males and females of C. undecimalis: positive allometry for females (P= 0.0022*L3.353) and negative allometry for males (P= 0.0108*L2.945). Both males and females of C. ensiferus showed a positive allometric relationship (P= 0.0049*L3.235). Lack of fishing regulations and controls, evidenced in this study by significant volumes of immature individuals in the catches, and the particular reproductive biology of these species, strongly indicates the need to establish regulations to ensure their responsible use. We recommend establishing a closed season during the first quarter of the year and minimum catch sizes for both species.